Phytochemical screening, antioxidant activity and in vitro biological evaluation of leave extracts of Hyptis suaveolens (L.) from south of Mexico - Sánchez Aguirre, Oscar (2020)
Hyptis suaveolens (L.) is a medicinally plant available in the south and southeast region of Mexico, Latin America and the south and west region of Africa. Infusion of this plant is used to treat diarrhea and as a muscle relaxant. In this study the antioxidant and antibacterial activity, and the phenolic compounds content of Hyptis suaveolens leaves was evaluated. The antioxidant activity was performed by DPPH (1,1-diphenyl-2-picryl-hydrazyl) method, obtaining an IC50 range of 2.73–3.58 μg/mL for the different prepared extracts. The content of phenolic compounds was carried out by Folin-Ciocalteu method, obtaining for the extracts an oscillation of 253.68–336.50 mg of GAE/g of extract. The antibacterial activity was evaluated by disc diffusion method against Staphylococcus aureus, Escherichia coli and Salmonella thipy, of the three pathogenic microorganisms evaluated, S. aureus showed a higher sensitivity to treatment with a minimum inhibitory concentration (MIC) of 0.25 μg/mL, for E. coli and S. typhi was 0.5 μg/mL. The results confirm the great potential of this species as an antioxidant and antibacterial representing the first contribution to the chemical and biological knowledge of H. suaveolens from Mexican mountain range.